Antihyperlipidemic Activity of Plectranthus Vettiveroides Roots - Gayathri Nallathambi; Jeevanandham Somasundaram; Mohammed Abdul Nazeer (International Journal of Allied Medical Sciences and Clinical Research, 2021)
Plant based Natural ingredients are important in the prevention and treatment of a variety of diseases and disorders in humans. Hyperlipidemia is a key clinical cause in heart disease and diabetes. Plectranthus vettiveroides, a member of the Lamiaceae family, was discovered to have anti-inflammatory, antibacterial, and anti-cancer properties, as well as CNS depressant properties. The current research uses an in vivo animal model to look at its antihyperlipidemic function. Dexamethasone administration causes a substantial rise in serum cholesterol and triglyceride (TG) levels, as well as an increase in the atherogenic index, in rats. The treatment of dexamethasone-induced hyperlipidemia in rats with an ethanolic extract of P.vettiveroides root (200 and 400 mg/kg) showed substantial inhibition by keeping cholesterol, TGs, and other serum levels near average.